2016
DOI: 10.1111/bju.13621
|View full text |Cite
|
Sign up to set email alerts
|

Actual lowering effect of metabolic syndrome on serum prostate‐specific antigen levels is partly concealed by enlarged prostate: results from a large‐scale population‐based study

Abstract: The actual lowering effect of MetS on serum PSA levels was partly concealed by the enlarged prostate in men with MetS, and the presence of MetS was independently associated with lower serum PSA levels. Urologists need to be aware of the effect of MetS on serum PSA levels and should discuss this subject with their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
3
0
4
Order By: Relevance
“…Another bias mechanism is that a high proportion of men with high socio‐economic status undergo PSA testing in the PSA era. It is well established that men with a high socio‐economic status have a lower prevalence of MetS and therefore have higher PSA levels, as indicated by the present report in the BJUI , and an elevated risk of PCa. Thus, multiple bias mechanisms seem to conceal low‐stage PCa in the PSA era.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Another bias mechanism is that a high proportion of men with high socio‐economic status undergo PSA testing in the PSA era. It is well established that men with a high socio‐economic status have a lower prevalence of MetS and therefore have higher PSA levels, as indicated by the present report in the BJUI , and an elevated risk of PCa. Thus, multiple bias mechanisms seem to conceal low‐stage PCa in the PSA era.…”
supporting
confidence: 67%
“…Zhao et al. address this specific question in this issue of BJUI and confirm that the presence of MetS was independently associated with a lower PSA level and that the enlarged prostate gland, which is an aspect of MetS, partly concealed an even greater PSA level reduction . The findings indicate that a bias mechanism inverses the link between MetS and incident PCa and support the above‐mentioned hypothesis.…”
mentioning
confidence: 71%
“…We also reported that as the number of abnormal components in MetS increases, the serum PSA level presents a trend of progressive decline. This study was based on a sample of 45,540 healthy men aged 55 to 59 [9]. However, the serum PSA level was not associated with MetS in our study, which may have been due to the small sample size.…”
Section: Discussionmentioning
confidence: 63%
“…Our previous study made investigate the association between MetS and serum PSA levels. We first found that the diagnosis of MetS decreased serum PSA levels by 11.3% compared to the absence of MetS after adjustment with a larger PV in MetS patients, at the same time, there is a linear relationship between the decrease of PSA and the number of components of metabolic syndrome [9].…”
Section: Introductionmentioning
confidence: 99%
“…(9) La fisiopatología de la obesidad incluye a la hiperinsulinemia, diabetes mellitus tipo 2, incremento de triglicéridos, citocinas proinflamatorias, proteínica C reactiva, hormonas sexuales esteroideas y aumento del factor de crecimiento similar a la insulina (IGF-1), esta última relacionada con la actividad mitogénica y antiapoptótica; (10) siendo relacionado a tumores de órganos sólidos. (10,11) A pesar que algunos estudios afirman que los pacientes con HBP y MetS tienen los valores más altos de PSA, (12,13) otros informaron que los niveles de PSA eran de aproximadamente 0.2-0.4 ng/ml más bajos entre los individuos que eran obesos, pero por lo demás sanos, en comparación con los no obesos; (10) por otro lado, en una población a gran escala en China se demostró que el efecto de disminución de MetS sobre los niveles de PSA se vieron ocultados en parte por el agrandamiento de la próstata en pacientes con MetS, y la presencia de MetS se asoció a niveles de PSA más bajos. Por último en otro estudio no hubo informes de correlación entre los niveles de PSA con los componentes del MetS.…”
Section: Antecedentesunclassified